The End of Playtime? The Time at Kindergarten and School from a Cultural-Theoretical Perspective - Hildebrandt, Elke; Weißhaupt, Mark (International Dialogues on Education Journal, 2018)
This article will, from the point of view of cultural theory, discuss the polarization that is frequently found between playful learning at the kindergarten and serious learning at school. Planning of the time in the German-speaking Swiss kindergarten is strongly influenced by the portent of preparation for school, which is combined with a reputedly vital transition from free playtime to planned curriculum-oriented learning time within a specific school order, additionally driven by a discourse on time pressure. The question is asked whether this is primarily a matter of “gaining time” for education, or whether it is about familiarizing the children with primary school culture as such. The question is asked: What potential for school-learning processes could possibly lie in play? Both cultures, that of the kindergarten as well as that of the primary school, are viewed as performance practices deeply rooted in historical, differing symbolic traditions.